Development and characterization of Pennisetum Purpureum/pla biocomposite scaffold - Radakisnin, Revati (School of Mechatronic Engineering, 2017)
The scope of this project is to establish the background study about the development and characterization of Purpureum pennisetum/PLA biocomposite as a tissue engineering scaffold. In this investigation, fabrications of the PLA composite scaffold with various P. purpureum contents will be prepared using solvent casting-particulate leaching technique. The composite scaffolds will be characterized using field emission scanning electron microscopy (FESEM), Fourier transform infrared spectroscopy (FTIR), x-ray diffraction (XRD), and thermogravimetric analysis (TGA). The compression testing will then be carried out by following ASTM F451-95; the compressed scaffold undergoes FESEM to study the impact on its microstructure. Further investigation on the in vitro degradation of composite scaffolds will be evaluated in this study. The prepared scaffolds will be immersed in phosphate buffered saline (PBS) medium for 40 days to determine the weight loss, pH changes, and water uptake and conduct the FESEM test on the degraded scaffolds.